1965
DOI: 10.2134/agronj1965.00021962005700030015x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stocking Pressure on Animal and Acre Output1

Abstract: Synopsis Daily gains of the steers on the lighter stocked pastures were greater than those on the heavier stocked pastures. However, a large difference in stocking pressure had to be imposed before the difference in either steer gains, carrying capacity, or herbage dry matter digestibility were significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1968
1968
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…These findings are in disagreement with those of other studies in which the relationship between ADG and stocking rate was linear (Mezzadra et al, 1992; Bransby et al, 1988; Hart, 1972; Bryant et al, 1965; Petersen et al, 1965; Riewe et al, 1963; Riewe, 1961), although Ashley (1993) and Oberholster (1990) also reported a quadratic relationship between ADG and stocking rate for annual ryegrass pastures and also for cereal rye ( Secale cereale L.).…”
Section: Resultscontrasting
confidence: 82%
“…These findings are in disagreement with those of other studies in which the relationship between ADG and stocking rate was linear (Mezzadra et al, 1992; Bransby et al, 1988; Hart, 1972; Bryant et al, 1965; Petersen et al, 1965; Riewe et al, 1963; Riewe, 1961), although Ashley (1993) and Oberholster (1990) also reported a quadratic relationship between ADG and stocking rate for annual ryegrass pastures and also for cereal rye ( Secale cereale L.).…”
Section: Resultscontrasting
confidence: 82%
“…As stocking rate increases, the output per animal declines but production per hectare increases (MCMEEKAN 1956, MOTT 1960, BRYANT et al 1965, PETERSEN et al 1965. Maxinium production per hectare is obtained when loss in production per animal by increasing the stocking rate is offset by the increased number of animals carried.…”
Section: Grazing Managementmentioning
confidence: 99%
“…Stocking rate affects animal performance both on a per animal and per ha basis (HEIN andViNALL 1933 andBRYANT et al 1965). Few experiments have been conducted in the region where stocking rates have been compared.…”
Section: Introductionmentioning
confidence: 99%
“…Few experiments have been conducted in the region where stocking rates have been compared. Stocking rate affects animal performance both on a per animal and per ha basis (HEIN andViNALL 1933 andBRYANT et al 1965). Stocking rate and grazing management affect pasture as.…”
Section: Introductionmentioning
confidence: 99%